Investigation of extended Y chromosome STR haplotypes in Sardinia. (March 2017) - Lacerenza, D.; Aneli, S.; Di Gaetano, C.; Critelli, R.; Piazza, A.; Matullo, G.; Culigioni, C.; Robledo, R.; Robino, C.; Calò, C.
Highlights: A large set of Y-STRs including rapidly mutating (RM) loci was studied in Sardinia. Complete differentiation of male lineages was impossible even by means of RM Y-STRs. Genetic heterogeneity was seen for isolated, but not for open Sardinian populations. RM Y-STRs confirm Sardinians as outliers in the Italian genetic landscape. Abstract: Y-chromosomal variation of selected single nucleotide polymorphisms (SNPs) and 32 short tandem repeat (STR) loci was evaluated in Sardinia in three open population groups (Northern Sardinia, n = 40; Central Sardinia, n = 56; Southern Sardinia, n = 91) and three isolates (Desulo, n = 34; Benetutti, n = 45, Carloforte, n = 42). The tested Y-STRs consisted of Yfiler ® Plus markers and the seven rapidly mutating (RM) loci not included in the YFiler ® Plus kit (DYF399S1, DYF403S1ab, DYF404S1, DYS526ab, DYS547, DYS612, and DYS626). As expected, inclusion of additional Y-STR loci increased haplotype diversity ( h ), though complete differentiation of male lineages was impossible even by means of RM Y-STRs ( h  = 0.99997). Analysis of molecular variance indicated that the three open populations were fairly homogeneous, whereas signs of genetic heterogeneity could be detected when the three isolates were also included in the analysis. Multidimensional scaling analysis showed that, even for extended haplotypes including RM Y-STR markers, Sardinians were clearly differentiated from populations of the Italian peninsula and Sicily. The only exception was represented by the Carloforte sample that, in accordance with its peculiar population history, clustered with Northern/Central Italian populations. The introduction of extended forensic Y-STR panels, including highly variable RM Y-STR markers, is expected to reduce the impact of population structure on haplotype frequency estimations. However, our results show that the availability of geographically detailed reference databases is still important for the assessment of the evidential value of a Y-haplotype match.